2008
DOI: 10.1165/rcmb.2007-0124oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Exposure to Particles during Pregnancy Causes Increased Neonatal Asthma Susceptibility

Abstract: Maternal immune responses can promote allergy development in offspring, as shown in a model of increased susceptibility to asthma in babies of ovalbumin (OVA)-sensitized and -challenged mother mice. We investigated whether inflammatory responses to air pollution particles (diesel exhaust particles, DEP) or control ''inert'' titanium dioxide (TiO 2 ) particles are enhanced during pregnancy and whether exposure to particles can cause increased neonatal susceptibility to asthma. Pregnant BALB/c mice (or nonpregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
141
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(159 citation statements)
references
References 51 publications
(53 reference statements)
8
141
2
5
Order By: Relevance
“…After such exposure, increased airway hyperresponsiveness, increased numbers of eosinophils, and pulmonary inflammation are found in offspring. 201 In vitro studies. The developmental toxicity of cobalt ferrite and gold nanoparticles has been investigated in vitro using the embryonic stem cell line ES-D3.…”
mentioning
confidence: 99%
“…After such exposure, increased airway hyperresponsiveness, increased numbers of eosinophils, and pulmonary inflammation are found in offspring. 201 In vitro studies. The developmental toxicity of cobalt ferrite and gold nanoparticles has been investigated in vitro using the embryonic stem cell line ES-D3.…”
mentioning
confidence: 99%
“…Studies examining prenatal and neonatal inhalation exposures to DE in rats have also shown increases in allergen-specific IgE responses in adults (Watanabe and Ohsawa, 2002). Aspiration studies of DEP as well as other more inert materials including titanium dioxide and carbon black at GD14 resulted in enhanced allergic airway inflammation during the preweaning period in murine offspring (Fedulov et al, 2008), although ambient particulate matter aspiration in pregnant C57BL6 dams increased airway hyperreactivity and inflammatory cytokines in the offspring postnatally exposed to 1 ppm O 3 (Auten et al, 2009). Due to the aforementioned studies, we hypothesized that maternal exposure to ozone could alter immune function of the offspring to increase development of allergic airway disease.…”
Section: Research Articlementioning
confidence: 99%
“…Adverse effects of prenatal exposure to engineered nanoparticles in vitro and in vivo have been summarized by (Ema et al, 2010;Hougaard et al, 2011). The effects observed in animals include altered immune response, development of the nervous system and reproductive function (Fedulov et al, 2008;Lamoureux et al, 2010;Shimizu et al, 2009;Takahashi et al, 2010;Takeda et al, 2009;Yoshida et al, 2009;Yoshida et al, 2010).…”
Section: Ambient Air Pollutionmentioning
confidence: 99%
“…Littering dams were assessed at the end of lactation after weaning (23-27 days after end of exposure). Pregnancy is reported to alter www.intechopen.com Maternal Exposure to Particulate Air Pollution and Engineered Nanoparticles: Reproductive and Developmental Effects 63 inflammatory response (Fedulov et al, 2008;Lamoureux et al, 2010), thus, different background levels in these sets of time-mated females were anticipated.…”
Section: Animal Modelmentioning
confidence: 99%